2014
DOI: 10.1088/0029-5515/54/6/064014
|View full text |Cite
|
Sign up to set email alerts
|

Study of the penetration of resonant magnetic perturbations in J-TEXT

Abstract: In the J-TEXT tokamak, the penetration of resonant magnetic perturbations (RMPs) has been studied by using a set of in-vessel RMP coils. It is found that, once the RMP amplitude exceeds a critical value, the applied RMP can lead to field penetration and excitation of a large locked mode in the tearing-stable plasma. The sawtooth oscillations disappear and the confinement deteriorates significantly accompanied by tearing mode excitation. For the plasma with an initial high frequency tearing mode, the RMP can su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 28 publications
7
70
1
Order By: Relevance
“…These results are different from the scaling of penetration threshold for 2/1 mode on other tokamaks, which usually scale in linear for the central density [45][46][47]. Another scaling Ic  ne 0.5 is also found on TEXTOR [48] and J-TEXT [49].…”
Section: Experimental Results With Static Rmpsmentioning
confidence: 77%
“…These results are different from the scaling of penetration threshold for 2/1 mode on other tokamaks, which usually scale in linear for the central density [45][46][47]. Another scaling Ic  ne 0.5 is also found on TEXTOR [48] and J-TEXT [49].…”
Section: Experimental Results With Static Rmpsmentioning
confidence: 77%
“…2(c) (also described previously in Ref. [46]). This indicates that the SMOs originated from the q = 2/1 surface and that f MHD ≈ 8 kHz at the 2/1 RS.…”
Section: Resultsmentioning
confidence: 99%
“…© IOP Publishing Ltd. All rights reserved. Figure 11 shows the dependence of mode penetration threshold on the electron density in J-TEXT [35]. It is found that the penetration threshold increases with increasing density with a density scaling 2/1 0.5 0.05 re bn  …”
Section: Thresholds During the Interaction Between Rmp And Tearing Modementioning
confidence: 99%
“…Recent J-TEXT research has contributed to the understanding of the interaction between RMP and tearing mode instabilities. This part summarizes the main findings, including the locking [26][27][28][29][30][31][32][33][34], suppression [26][27][28][29], excitation [35] of the tearing mode and the corresponding thresholds of RMP.…”
Section: Interaction Between Rmp and Tearing Modementioning
confidence: 99%
See 1 more Smart Citation